Tinjauan Hukum Islam Terhadap Pelaksanaan Asuransi Pembiayaan Murabahah di BPRS X Provinsi Riau - Uswatun Khasanah (Jurnal Ilmiah Ekonomi Islam, 2021)
Financial insurance in Islamic banking is carried out as one of the risk management as an effort to maintain bank stability. Based on OJK regulations Number 23/POJK.03/2018 regarding Application of Risk Management for Sharia Rural Banks (BPRS), BPRS have to carry out the process of identification, measurement, monitoring and risk control of all material risk factors. This research is a field research through a normative juridical approach. This research aims to see the implementation of financing insurance in BPRS X and to see the suitability of the implementation of financing insurance against Sharia principles. The results showed that the implementation of murabahah financing insurance at BPRS X is optional. The customer can choose not to pay for life insurance and assign responsibility to the heirs if the customer dies. However, in practice the Bank continues to register insurance even without the consent of the customer. So that the implementation of financing insurance at BPRS X is not fully in accordance with Islamic law. Because in Fiqh study, the practice of Murabahah is carried out by prioritizing the principles of honesty, transparency, openness and Islamic values.